Manifestation of gender bias [videorecording] - Abraham, Rebecca Demetillo; David, Karina Constantino (Harnessing Self Reliant Initiatives and Knowledge (HASIK) with the support of Philippine Canada Human Resource Development (PC-HRD) Program, 1995)
A lecture concert on gender oppression, gender bias and gender inequality.